2017
DOI: 10.1093/imaiai/iaw023
|View full text |Cite
|
Sign up to set email alerts
|

Weighted ${\ell}_{{1}}$-minimization for sparse recovery under arbitrary prior information

Abstract: Weighted ℓ 1 -minimization has been studied as a technique for the reconstruction of a sparse signal from compressively sampled measurements when prior information about the signal, in the form of a support estimate, is available. In this work, we study the recovery conditions and the associated recovery guarantees of weighted ℓ 1 -minimization when arbitrarily many distinct weights are permitted. For example, such a setup might be used when one has multiple estimates for the support of a signal, and these est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
(102 reference statements)
0
20
0
Order By: Relevance
“…It is again confirmed that a multi-level weighting scheme can enhance the recovery performance. The tuning of the weights in [11] is achieved based on empirical results rather than theoretical findings.…”
Section: B Related Work and Key Differencesmentioning
confidence: 99%
“…It is again confirmed that a multi-level weighting scheme can enhance the recovery performance. The tuning of the weights in [11] is achieved based on empirical results rather than theoretical findings.…”
Section: B Related Work and Key Differencesmentioning
confidence: 99%
“…There have also been some research efforts that aim at exploiting additional knowledge about the signal to further improve the sensing information recovery [23][24][25][26][27][28][29]. For instance, [23] proposes a ℓ 1 −minimization based approach that exploits knowledge about the support 1 of the sparse signal to recover information from noise-free measurements.…”
Section: A Related Workmentioning
confidence: 99%
“…They show that this recovery approach is more stable and robust than standard ℓ 1 −minimization approaches when 50% of the support is estimated correctly. This approach has been generalized for multiple weights in [25], addressing the case where the support is estimated with different confidence levels. These approaches, however, work well in applications where the support does not change much over time, like real-time dynamic MRI [23] and video/audio decoding [24,25] applications.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the analysis based problem (Equation )), the greedy‐type algorithms such as Greedy Analysis Pursuit 12‐14 or thresholding‐based methods such as iterative hard thresholding (IHT) have been proposed 15 . Several modifications of the greedy algorithms, incorporated partially known support information, have been performed for compressed sensing 16 . Modification of the IHT, 17 Binary Iterative Hard Thresholding (BIHT), 18 Orthogonal Matching Pursuit (OMP), 19 Compressive Sampling Matching Pursuit (CoSaMP), 20 and re‐weighted least squares 21 algorithms were studied in References 22‐24.…”
Section: Introductionmentioning
confidence: 99%